A DFT study of As doped WSe2: A NO2 sensing material with ultra-high selectivity in the atmospheric environment. (September 2021) - Wang, Zhaokun; Gao, Chenshan; Hou, Shuhan; Yang, Huiru; Shao, Ziyuan; Xu, Siyuan; Ye, Huaiyu
Abstract: In this work, the adsorption of toxic gaseous NO2 and other gas molecules (NO, CO, CO2, N2, O2, SO2 ) on pristine and X-doped (X = Si, P, S, Te, As) two-dimensional (2D) WSe2 have been detailed studied by performing density functional theory (DFT) calculations. Calculation results of adsorption energies and adsorption distances demonstrate that As-doped 2D WSe2 (As-WSe2 ) exhibits high selectivity not only towards NO2, but also towards NO and SO2 . However, the charge transfer between NO and the substrate is too small to detect, and chemical bond forms between SO2 and the substrate; both phenomena make As-WSe2 substrate more suitable as a substrate material of the NO2 sensor. To eliminate the interference of SO2 on the adsorption of NO2, coexistence of NO2 and SO2 is simulated. Results reveal that although the interaction between SO2 and the As-WSe2 substrate is stronger than that between NO2 and the substrate, SO2 molecule hardly interacts with the substrate when co-adsorbed with NO2 . Besides, calculation results of DOS and PDOS further confirm the sensitivity of As-WSe2 towards NO2 ; and those of the recovery time also highlight the extremely fast recovery rate of As-WSe2 after adsorbing NO2 . The present findings make As-WSe2 monolayer a potential substrate material of NO2 gas sensors used in the atmospheric environment. Graphical Abstract: ga1 Highlights: The interactions between five doped two-dimensional WSe2 substrates and seven gases including NO2 are analyzed and compared in detail. Two-dimensional As-WSe2 has sufficiently strong selectivity and sensitivity towards NO2 in the atmospheric environment. As the temperature rises, NO2 can be quickly desorbed from the surface of two-dimensional As-WSe2 .